2008
DOI: 10.1210/jc.2007-1692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graded Doses of Testosterone on Erythropoiesis in Healthy Young and Older Men

Abstract: Testosterone has a dose-dependent stimulatory effect on erythropoiesis in men that is more pronounced in older men. The testosterone-induced rise in hemoglobin and hematocrit and age-related differences in response to testosterone therapy may be mediated by factors other than erythropoietin and sTfR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
233
3
12

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 325 publications
(264 citation statements)
references
References 33 publications
9
233
3
12
Order By: Relevance
“…61 In another study, testosterone was shown to dose-dependently increase the Hb/haematocrit rate, but did not show a related increase in erythropoietin. 62 A recent study observed increased human erythropoiesis as a result of the acceleration of the conversion of dehydroepiandrosterone sulphate (DHEAS) to testosterone by activation of 3-beta-hydroxysteroid dehydrogenase 2 (3beta-HSD2) and/or 17beta-HSD3, resulting in high serum testosterone levels and high Hb levels. 63 The conversion of testosterone to dihydrotestosterone 64 or to oestradiol 65 is not essential for the mediation of its effects on erythropoiesis.…”
Section: Testosterone and Erythropoiesismentioning
confidence: 99%
“…61 In another study, testosterone was shown to dose-dependently increase the Hb/haematocrit rate, but did not show a related increase in erythropoietin. 62 A recent study observed increased human erythropoiesis as a result of the acceleration of the conversion of dehydroepiandrosterone sulphate (DHEAS) to testosterone by activation of 3-beta-hydroxysteroid dehydrogenase 2 (3beta-HSD2) and/or 17beta-HSD3, resulting in high serum testosterone levels and high Hb levels. 63 The conversion of testosterone to dihydrotestosterone 64 or to oestradiol 65 is not essential for the mediation of its effects on erythropoiesis.…”
Section: Testosterone and Erythropoiesismentioning
confidence: 99%
“…In a recent study it was convincingly confirmed that npg testosterone has a dose-dependent stimulatory effect on hematopoiesis in men. Remarkably, this effect was more pronounced in older men [121]. Also other studies confirmed the relevance of the dose of testosterone [126] and of age as factors in the stimulation of hematopoiesis [127].…”
Section: Polycythemiamentioning
confidence: 59%
“…Testosterone deficiency results in a 10% to 20% decrease in the blood hemoglobin concentration, which can result in anemia [120,121]. Young hypogonadal men usually have fewer red blood cells and lower hemoglobin levels than age-matched controls, whilst healthy older men also may have lower hemoglobin than normal young men.…”
Section: Improving Anemiamentioning
confidence: 99%
“…Testosterone increases erythropoetin levels, but the erythropoetin levels return towards baseline with a continued testosterone therapy (23). However, erythropoetin levels are elevated in relation to the increased haemoglobin levels in testosterone-treated men.…”
Section: Discussionmentioning
confidence: 96%